Decisional regret in women receiving high risk or inconclusive prenatal cell-free DNA screening results. (17th April 2020) - Gammon, Betsy L.; Jaramillo, Carolina; Riggan, Kirsten A.; Allyse, Megan
Abstract: Objectives: This study examined the experiences of women receiving high-risk cell-free DNA (cfDNA) screening results, with particular focus on decisional satisfaction after receiving high-risk, false, or inconclusive results. It is already known that cell-free DNA screening is rapidly expanding in the clinical practice. A growing number of women are offered cfDNA screening for an increasingly broad range of chromosomal and microdeletion syndromes. However, research shows that the very low false positive rate attributed to cfDNA screening for trisomy 21 does not apply to other conditions. Methods: As a part of the larger study on patient experiences, 40 semistructured telephone interviews were conducted with women who were, or had recently been, pregnant and received high-risk ( n  = 15), false positive/negative ( n  = 20), or inconclusive ( n  = 5) results from cfDNA screening. Results: One third of participants would not elect to have cfDNA screening in a future pregnancy, and another third would only have the screen under particular circumstances or if the scope of the panel was limited. Many women reported feeling misled by the information they received prior to accepting cfDNA screening or receiving their results. Conclusions: Study participants described issues with the clinical dialog when cfDNA screening is offered; when results are returned; and problems with the availability of information about the existence of false positives. These reports suggest that inadequate pretest discussion contributes to women's experience of decisional regret after receiving high-risk, false positive, or inconclusive results. Given the confusion about cfDNA screening accuracy, the prevalence of follow-up invasive tests, and the number of women who reported that they regretted choosing cfDNA screening, the mode of offering cfDNA should be reassessed.